English syllabus proposals in the service area for Arts and Biology schools - Funes Rivera, Gustavo Adolfo; Mendoza Villalobos, Ada Esteli; Orellana Cruz, Ana Silvia; Pérez Ramírez, Roxana Marisol; Salazar Murcia, Pedro Antonio; Garay Salinas, Ricardo (San Salvador : Universidad de El Salvador, 2012)
The main purpose of this project is to propose a new syllabus proposal for the English Service Area in the majors of Arts and Biology by identifying the main students’ needs according to each academic profile during the second term 2011 of the “Licenciaturas en Artes Plásticas y Biología de la Universidad de El Salvador” The research team took into consideration the analysis of syllabi from 2006 to 2011 of the English Service Area; also, the biology and arts students, the authorities of “Facultad de Ciencias Naturales” and “Escuela de Artes” interviews, for proposing a new syllabus for both majors. Summing up, it is important to make a deep and conscientious study of the real students’ necessities and apply them into the syllabus design; that is why the significance of this project.
Anexos. diagnosis, syllabus proposal for Biology Major, syllabus proposal for Art Major, analysis of syllabi.
Tesis -- (Licenciatura en Idioma Inglés, opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2012
Bibliografía : hoja 62
Audiencia general
Texto en inglés con algunas frases en español
Keywords: Inglés -- Enseñanza; Lenguaje y lenguas -- Enseñanza; Currículo